Gestão Global da Capacidade Relacional. Um Estudo com as Multinacionais Brasileiras - Priscila Rezende da Costa (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
Innovation and its dispersion and interaction attributes are essential for any business to be successful. Given this scenario, we aimed at evaluating how the global management of relational capability takes place in Brazilian multinationals. We conducted a qualitative research with a descriptive nature. Multiple-case method was used since two Brazilian multinationals, Braskem and Petrobras, were analyzed in deep. As a result, we could conclude that the global management of relational capability permeates headquarters, subsidiaries and national and international technology partners. For this reason, adopting dynamic and collaborative managerial practices is relevant, and these practices include: adapting and aligning to the opportunities, collaborative R&D structure, a diversified portfolio of technology partners, shared planning of open innovation practices, shared organization of open innovation practices, collaborative knowledge management and synergic monitoring of interactions.